Стихи и рассказы о Родине: [для среднего школьного возраста / художники: Белозерцев Д. [и др.]] - Белозерцев Д. (РОСМЭН, 2015)
Экземпляры: ДБ (20200831) / Инвентарный номер: 52888 / Цена: 267.00 / Сис.шифр: 84(2Рос=Рус) / Авт.знак: С 80 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)